PELATIHAN KOMPUTERISASI AKUNTANSI DENGAN APLIKASI SISKEUDES DALAM UPAYA PENINGKATAN KOMPETENSI GURU - Yustrianthe, Rahmawati Hanny; Darmawan, Yanto; Jati, Budhi Purwantoro; Kuntoro, Agus (Jurnal Terapan Abdimas, 2022)
Abstract. Village funds provided by the central government aim to encourage the productivity of rural communities. For this reason, the use of village funds must be planned, implemented and reported to assess the level of success of the village fund program as stated in Law Number 6 concerning Villages of 2014 and Ministerial Regulation Number 113. This attracts the attention of all parties, including the world of education, considering that the central government funds disbursed to villages reaches 10% of the total state budget. Therefore, a clear, transparent and easy accountability system is needed for village financial management. In this regard, BPKP in collaboration with the Ministry of Home Affairs has developed the SISKEUDES application which is expected to fulfill these objectives. The world of education, especially at the vocational level, tries to follow up on this need by incorporating digital-based village accounting materials into its curriculum so that it is able to provide the necessary skilled workers. In order to bridge the needs and make the success of the above government program a success, community service activities are carried out to improve and strengthen the competence of accounting teachers at SMK DIY and Central Java towards the village financial system and the operation of the siskeudes application system. The service team from the YKPN Polytechnic will hold community service in 2021 with the theme: "Computerized Accounting Training with the Siskeudes Application in the Context of Improving Teacher Competence". The method used in this activity is the lecture method, tutorial, practice and discussion of training and teaching theory and application of the village financial system. The training was attended by 46 teachers which was carried out offline at the YKPN Yogyakarta Polytechnic Building. The result of this service is that accounting teachers at MGMP Accounting DIY and Central Java are increasingly competent in teaching computerized village accounting. This can be seen from the smooth implementation as planned and the enthusiasm of the participants in completing the material in the village accounting computer module. In addition, it can also be seen from the feedback given by the vocational teachers who participated in the training who expressed satisfaction, felt the benefits of the training to increase their knowledge and skills related to the SISKEUDES application. After this service activity, it is hoped that what has been obtained by the teacher can be implemented in their SMKs so that they can produce students who are competent and able to play a major role as operators in operating the siskeudes application. The teachers also hope that similar training can be carried out again with a wider audience, and with other topics. Abstrak. Dana desa yang diberikan oleh pemerintah pusat bertujuan untuk mendorong produktivitas masyarakat desa. Untuk itu penggunaan dana desa harus direncanakan, dilaksanakan dan dilaporkan untuk menilai tingkat keberhasilan program dana desa sebagaimana tertuang dalam Undang-Undang Nomor 6 tentang Desa Tahun 2014 dan Peraturan Menteri Nomor 113. Hal ini menarik perhatian semua pihak. , termasuk dunia pendidikan, mengingat dana pemerintah pusat yang dikucurkan ke desa mencapai 10% dari total APBN. Oleh karena itu, diperlukan sistem pertanggungjawaban yang jelas, transparan dan mudah dalam pengelolaan keuangan desa. Berkaitan dengan hal tersebut, BPKP bekerjasama dengan Kementerian Dalam Negeri telah mengembangkan aplikasi SISKEUDES yang diharapkan dapat memenuhi tujuan tersebut. Dunia pendidikan khususnya pada tingkat vokasi mencoba menindaklanjuti kebutuhan tersebut dengan memasukkan materi akuntansi desa berbasis digital ke dalam kurikulumnya sehingga mampu menyediakan tenaga terampil yang diperlukan. Dalam rangka menjembatani kebutuhan dan menyukseskan program pemerintah di atas, maka dilakukan kegiatan pengabdian kepada masyarakat untuk meningkatkan dan memperkuat kompetensi guru akuntansi di SMK DIY dan Jawa Tengah terhadap sistem keuangan desa dan operasionalisasi siskeudes. sistem aplikasi. Tim pengabdian dari Politeknik YKPN akan mengadakan pengabdian masyarakat pada tahun 2021 dengan tema : “Pelatihan Akuntansi Komputerisasi dengan Aplikasi Siskeudes Dalam Rangka Peningkatan Kompetensi Guru”. Metode yang digunakan dalam kegiatan ini adalah metode ceramah, tutorial, praktek dan diskusi teori pelatihan dan pengajaran serta penerapan sistem keuangan desa. Pelatihan diikuti oleh 46 guru yang dilaksanakan secara offline di Gedung Politeknik YKPN Yogyakarta. Hasil dari pengabdian ini guru akuntansi di MGMP Akuntansi DIY dan Jawa Tengah semakin kompeten dalam mengajar akuntansi desa yang terkomputerisasi. Hal ini terlihat dari kelancaran pelaksanaan sesuai rencana dan semangat peserta dalam menyelesaikan materi pada modul komputer akuntansi desa. Selain itu juga dapat dilihat dari feedback yang diberikan oleh para guru SMK peserta pelatihan yang menyatakan puas, merasakan manfaat dari pelatihan tersebut untuk menambah pengetahuan dan keterampilannya terkait dengan penerapan SISKEUDES. Setelah kegiatan pengabdian ini diharapkan apa yang telah diperoleh guru dapat diimplementasikan di SMK-nya sehingga dapat menghasilkan siswa yang berkompeten dan mampu berperan utama sebagai operator dalam mengoperasikan aplikasi siskeudes. Para guru juga berharap agar pelatihan serupa dapat dilakukan kembali dengan audiens yang lebih luas, dan dengan topik lain.